Adjustments and Constraints: Biden Administration's Iran Policy. Issue 2 (3rd April 2022) - Tang, Jiahua; Pan, Rui
Abstract: This article provides an overview of the recent US Iran policies by comparing the US Middle East strategy under the Biden administration to the Trump administration's approach. Trump's 'maximum pressure' campaign adopted various aggressive policies including withdrawing from the Iran nuclear agreement and escalating sanction measures against Iran. However, the campaign has proven a failure as it was impeded by Iran's countermeasures and has damaged the US international reputations. The Biden administration has incentives to improve the US-Iran relations and restore the Iran nuclear deal. However, it faces constraints from both domestic politics and distrust of US alliances. Domestic hardliners have pressured the Biden administration to keep a tough stance on Iran and opposed the US to make concessions as it renegotiates the nuclear deal. Other related countries including the US allies are hesitant to comply with US. In terms of its Middle East strategy, Trump's betrayal of the previous deal has brought credibility crisis to the US. Though the Iran nuclear talks have restarted, the future of Iran's nuclear program remains bleak. Divergence is brewing among the US, Iran, and other related powers due to different national interests. Also, the newly elected Iranian presidency, led by ultra conservative leader Ebrahim Raisi's, makes a new Iran nuclear deal more difficult to obtain. To revive the Iran nuclear agreement, this article suggests that the Biden administration ensure Iran's interests through cooperation and pay more attention to the social development and people's livelihood in Iran.